Kindergarten Teachers’ Strategies In Facing The Implementation Of The Merdeka Belajar Curriculum - Ibdaul Latifah Ibdaul Latifah; Umi Sakhiyatul Millah1 (Universitas muhammadiyah Banjarmasin, 2024)
The changes to the Merdeka Belajar Curriculums that are currently being widely discussed have a big influence on changes in learning carried out by teachers. Even though curriculum changes often occur, in reality there are still many teachers who are not ready for these changes. This research aims to find teachers' strategies in dealing with the implementation of the Merdeka Belajar Curriculums, especially in early childhood education institutions. This research is of a qualitative type with data collection techniques in the form of observation, interviews and documentation. The data sources used in this research are kindergarten teachers who have implemented the Merdeka Belajar curriculums as well as several supporting documents such as research journals related to the Merdeka Belajar curriculums. The results of this research are that the strategies that teachers can apply in facing the implementation of the Merdeka Belajar curriculums are by purchasing several independent learning books, adding educational game tools, attending various seminars, workshops, webinars related to the Merdeka Belajar curriculums, interacting frequently with colleagues and read information related to the Merdeka Belajar curriculums from print media, the internet, and from teacher WhatsApp groups